The Struggle to Accept Rohingya Refugees in the Perspective of Law and Human Rights - Roni Sulistyanto Luhukay (Universitas Djuanda, 2025)
The Indonesian people believe that protecting human rights is necessary for ethnic Rohingya seeking asylum in Indonesia, as part of their commitment to being a country that upholds the spirit of the constitution. Indonesia has sovereignty and has not ratified the 1951 Convention or the 1967 Protocol, but it is still subject to general international law standards that are accepted and recognized internationally. Indonesia has an international obligation to comply with the provisions of the convention and protocol, despite the fact that it has not ratified them. It should be noted that norms that have not been ratified into national law do not have absolute legal force, which means that international legal norms can be violated as long as national interest does not require it. The research employs normative legal research methods. This study delves deeper into the protection of Rohingya refugees' human rights as a humanitarian response with implications for societal injustice. This can be seen in the absence of obligations as the fulfillment of rights carried out by Rohingya refugees receiving benefits without burden, or Rohingya refugees taking in greater benefits from the Indonesian people without burden. Furthermore, there are implications for the destruction of the socio-cultural order in the form of inherited knowledge, norms, regulations, and skills among Indonesians. This can be seen in the behavior and actions of Rohingya refugees who do not maintain cleanliness, do not adhere to Islamic law and customs within the community, do not follow local norms and customs, and commit criminal acts of rape on minors.